-2(u-7)=3u-11

Simple and best practice solution for -2(u-7)=3u-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(u-7)=3u-11 equation:


Simplifying
-2(u + -7) = 3u + -11

Reorder the terms:
-2(-7 + u) = 3u + -11
(-7 * -2 + u * -2) = 3u + -11
(14 + -2u) = 3u + -11

Reorder the terms:
14 + -2u = -11 + 3u

Solving
14 + -2u = -11 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
14 + -2u + -3u = -11 + 3u + -3u

Combine like terms: -2u + -3u = -5u
14 + -5u = -11 + 3u + -3u

Combine like terms: 3u + -3u = 0
14 + -5u = -11 + 0
14 + -5u = -11

Add '-14' to each side of the equation.
14 + -14 + -5u = -11 + -14

Combine like terms: 14 + -14 = 0
0 + -5u = -11 + -14
-5u = -11 + -14

Combine like terms: -11 + -14 = -25
-5u = -25

Divide each side by '-5'.
u = 5

Simplifying
u = 5

See similar equations:

| n+6=24 | | 30X^2=54X | | 10x+30=20-11x | | x/3-1=x/2 | | 152=4*8*4+2*4*h | | 4x+-10=38 | | 37+x=118 | | x/7-5=x/2 | | x/6-x/12+2=x+2 | | 0.01(x+5)-0.05=0.01(6x+5) | | 5.267-0.533=x | | 56x^2=16x | | 2.367-(1.45+1.45)=x | | 2.367+1.45+1.45=x | | 2.367+1.45=x | | 2.367+1.45= | | 0.01(x+5)-0.05=(6x+5) | | x-25=137 | | 6x+3(x-30)=63-x+3 | | 7x-9-10x-1= | | (2x-1)(x+2)=49 | | 9x-(5x+1)-[2+8x-(7x-5)]+9x=0 | | -3x-2/10=0.2x+4/3 | | 14*x^4+3x^2-28=0 | | 4-18=4x-6-3x | | 20x+3=-15 | | 4*0=x | | 3x-2y-(2x-3y)= | | 5(x+3)+2=5(x-8)-3x | | 3x+0-12=0 | | 3x^2+9x=6 | | 5(x-3)+2=5(x-8)-3x |

Equations solver categories